ENONTEKIÖ ART PATH - ENONTEKIÖN TAIDEPOLKU : a practical framework for sustainable community art projects in Finnish Lapland using service design tools - Mishra, Amisha (fi=Lapin yliopisto|en=University of Lapland|, 2019)
The following study presents a practical framework for sustainable community art projects based on the Enontekiön taidepolku or Enontekiö Art Path project (will be called the latter throughout the thesis). Enontekiö Art Path is a collaborative project between the University of Lapland and Municipality of Enontekiö in Finnish Lapland. The art path is formed by six different art workshops that moved from the village of Hetta all the way to the village of Kilpisjärvi during the years 2017–18. The aim of the project is to create environmental artworks based on local stories, traditions, and materials that the people in each village shared with the team of students and staff from the University of Lapland. This study has various objectives: first, to demonstrate the potential of art and artistic practices in the empowerment of the ageing members of the communities; second, to depict the significance of service design thinking and co-creation in community art projects; third, to present a practical framework for sustainable community art projects using service design thinking particularly in Finnish Lapland. The research strategy is arts-based action research. The main working methods were place-specific research, observations, note-taking, and documentation. A major outcome of this study is a practical framework for community art projects utilizing participatory service design tools, which can be used by the future Arctic Art and Design (AAD) students at the University of Lapland if they plan to continue the art path to other villages of Enontekiö municipality. Another outcome which is part of artistic practice is a publication designed for the community members and municipality website. Hence the results of this study are substantial and useful at both general and personal levels. At a personal level, the results are useful in terms of gained knowledge, experience, skills, and empathy together with an increased sense of responsibility towards older populations of the society. On a general level, the results aim to ...